On the formations of the Pampas in the footsteps of Darwin: South of the Salado - Zárate, M. (2009)
In 1833 during his journey across the Buenos Aires Pampas, Charles Darwin made observations that reflected his thoughts on two major landscape units, Pampa interserrana and Pampa deprimida, later identified by other authors. Darwin grouped the Pampean sediments into a single unit, the Pampean Formation, based upon the lithological homogeneity and the large extension of the deposits; the unit was thought to be of estuarine-marine origin and attributed to the Recent Epoch considering the paleontological content (vertebrates and mollusks). At present, the Pampean sedimentary succession, which accumulated approximately during the last 11-12 Ma, is interpreted as a pedosedimentary sequence due to the ubiquity of pedogenetic features throughout the deposits. Four main subcycles of sedimentation are identified related to reactivations of the Pampean landscape. At a regional scale, the outcrop distribution of Pampean sediments of different ages suggests the dominance of more stable conditions since the late Miocene-Pliocene in a vast area of Pampa interserrana, documented by the formation of calcretes. However, sedimentation during the late Pliocene-Pleistocene was active within the domain of the Salado tectonic basin and Sierras de Tandil. The regional disparity shown by the Pampean stratigraphic record reveals the major morphostructural differences of its basement.